Ballroom and Latin rhythms (Journal of Parents and Teachers, 2014)
More often related to party than to school, dancing is an educational tool to develop basic competencies in our primary students, who will learn and enjoy to the rhythm of music. It has formative and curricular advantages and methodology needs to be taken care of to introduce new dances gradually and progressively. In addition this article has planned sessions for every primary year.
Keywords: didactics; educational resource; physical education; ball dancing; latin rhythms; PE in primary.